“Die deutsche Grammatica … von Charmyntes” (Berlin, 1713): Creation, Author and Readers - Kareva, Natalia V.; Pivovarov, Evgeny G. (Slavistica Vilnensis, 2021)
The first printed German language grammar, created for Russians, “Die deutsche Grammatica <…> von Charmyntes” was published in Berlin, in 1713. The authors investigate its extant copies, paying particular attention to the variants, held in the Russian Academy of Sciences and the Russian National Library. They verify the assumption, stated by K. Koch (2002), that J. L. Frisch was the compiler of the manual, and discuss, why he might hide under the odd alias “Charmyntes”. The scholar’s biography and scientific legacy are succinctly outlined. Frisch’s role in the establishment of the first Russian-German coterie is considered. He taught several noble students from Russia (first — the Golovkins, especially Alexander, his long-time friend and collaborator; and then — “Moscowitische Prinzen oder Knaesen” — the Dolgorukies and Repnins). Frisch’s works were purchased for Russian private and public libraries. Some of them could be presented to the scholars (G. F. Müller) or aristocrats (tsarevna Maria Alekseyevna), visiting him. The authors suggest hypotheses, why Charmyntes did not want to reveal his real name and his possible encouragers: Muscovite acquaintances or German patrons. “Die deutsche Grammatica” was published in the year momentous for Prussian foreign affairs. The new king was establishing allied relations with Peter I. The country gradually waded into the Great Northern War.